The Use of Biologic Therapies in the Treatment of Rheumatoid Arthritis - Wang, Dashan; Li, Yan; Liu, Yuan; Shi, Guixiu (Current Pharmaceutical Biotechnology, 2014)
The use of biologic agents has revolutionized the management of rheumatoid arthritis (RA) in the past two decades. These biologic agents directly target molecules and cells involved in the pathogenesis of RA. Biologic agents indeed lead to a better prognosis and clinical remission in patients with RA, especially in patients who are not well-controlled with traditional disease-modifying anti-rheumatic drugs (DMARDs). Currently, five TNF inhibitors (infliximab, etanercept, adalimumab, golimumab and certolizumab pegol), an IL-6 receptor antagonist (tocilizumab), an IL-1 receptor antagonist (anakinra), a B cell depleting agent (rituximab) and a T cell co-stimulation inhibitor (abatacept) have been approved for the treatment of RA. With the increased understanding of the pathogenic mechanisms of RA and advantages in manufacturing biotechnology of pharmaceutical companies, a series of novel biologic therapeutic approaches are being developed. In the present paper, we will summarize the biologic agents currently available to treat RA, and the prospective biologic therapies that might be used in the management of RA in future.
Keywords: cell-targeted therapy